The role of neutrophils in the pathogenesis of ischemic stroke - I. I. Dolgushin; Z. Z. Zaripova; M. I. Karpova (Бюллетень сибирской медицины, 2021)
Background. Immune responses and inflammation play an important role in the pathogenesis of ischemic stroke.Aim. To analyze the involvement of neutrophils in the pathogenesis of ischemic stroke.Results. Data on the contribution of neutrophil granulocytes to the development of local sterile inflammation and secondary brain injury in acute ischemic stroke were summarized. Mechanisms of neutrophil influence on thrombosis, neutrophil extracellular trap formation (NETosis), protease release, and direct interaction with platelets with subsequent formation of platelet-leukocyte aggregates were discussed. Available information on the effectiveness of reperfusion therapy and an association of changes in neutrophil activity with development of infectious complications of stroke were presented. In addition, research data were presented on the contribution of neutrophils to atherogenesis, which is one of the most important etiological factors in ischemic stroke. The review showed that the contribution of neutrophils to the pathogenesis of ischemic stroke is associated with implementation of their secretory, regulatory, and phagocytic functions, as well as with NETosis.Conclusion. It was shown that neutrophils are involved in the pathogenesis of ischemic stroke and modulate a response to treatment.